Promotion of a Reaction by Cooling: Stereoselective 1, 2‐cis‐α‐Thioglycoconjugation by Thiol‐Ene Coupling at −80 °C. Issue 18 (8th March 2018) - Eszenyi, Dániel; Kelemen, Viktor; Balogh, Fanny; Bege, Miklós; Csávás, Magdolna; Herczegh, Pál; Borbás, Anikó
Abstract: The photoinitiated thiol‐ene coupling reactions of 2‐substituted glycals were studied as a generally applicable strategy for stereoselective 1, 2‐ cis ‐α‐thioconjugation. Although all glycals reacted with full α‐selectivity, the efficacy of the reactions varied in a broad range depending on their configuration and glycals bearing axial acetoxy substituents reacted with very low efficacy at room temperature. The study revealed that the reaction progress could be promoted by cooling and inhibited by heating. At −80 °C, the equilibrium of the rapidly reversible addition of the thiyl radical to alkenes is shifted almost completely toward products, leading to efficient addition reactions. By exploiting this unique temperature effect a series of α‐thio‐l ‐fucosides, ‐d ‐galactosides, and d ‐GlcNAc derivatives were prepared with high efficacy and complete stereoselectivity. Abstract : Sulfur sugars : Reaction temperature influences the thiol‐ene reactions of cyclic alkenes in a very unique fashion: cooling promotes whereas heating inhibits the reaction. Unfavorable steric and electronic effects resulting in low conversions at room temperature were overcome by conducting the reactions at −80 °C. The thiol‐ene coupling reaction of 2‐substituted hexoglycals at −80 °C is an efficient strategy for stereoselective 1, 2‐ cis ‐α‐thioconjugation.